The hot hand in professional darts - Marius Ötting; Roland Langrock; Christian Deutscher; Vianey Leos-Barajas (Journal of the Royal Statistical Society: Series A (Statistics in Society), 2019)
We investigate the hot hand hypothesis in professional darts in a nearly ideal setting with minimal to no interaction between players. Considering almost 1 year of tournament data, corresponding to 167492 dart throws in total, we use state space models to investigate serial dependence in throwing performance. In our models, a latent state process serves as a proxy for a player's underlying form, and we use auto-regressive processes to model how this process evolves over time. Our results regarding the persistence of the latent process indicate a weak hot hand effect, but the evidence is inconclusive.
Keywords: 519; Hidden Markov model; Hot hand; Sports statistics; State space model; Time series